Circumstances Impacting Cost of Equity through Integrated Reporting: A Competitive Analysis of Indonesian Companies - Defia Nurbatin; I Made Narsa (Jurnal Akuntansi dan Keuangan, 2026)
This study investigates how the integrated reporting (IR) framework influences the cost of equity (COE) among 115 non-financial firms listed on the Indonesia Stock Exchange from 2016 to 2020. The IR disclosure index is developed through content analysis of companies’ annual reports, while COE is estimated using the Capital Asset Pricing Model (CAPM). The findings reveal that higher IR coverage corresponds to an increase in COE in the subsequent year, indicating that comprehensive disclosure does not immediately reduce equity financing costs. The findings offer insights for regulators in designing standardized IR policies, for investors in evaluating informational credibility in emerging markets, and for firms in improving disclosure practices to enhance market confidence. Future research is encouraged to examine longer post-implementation periods and element-specific IR indicators.